2016
DOI: 10.1016/j.neuroimage.2015.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the resting-state fMRI global signal amplitude between the eyes open and eyes closed states are related to changes in EEG vigilance

Abstract: In resting-state functional connectivity magnetic resonance imaging (fcMRI) studies, measures of functional connectivity are often calculated after the removal of a global mean signal component. While the application of the global signal regression approach has been shown to reduce the influence of physiological artifacts and enhance the detection of functional networks, there is considerable controversy regarding its use as the method can lead to significant bias in the resultant connectivity measures. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 60 publications
9
100
0
Order By: Relevance
“…The utility of using SEC in the context of fMRI recordings was recently explored in two studies. The first study documented differences in resting-state fMRI global signal amplitude between eyes-open and eyes-closed states to EEG vigilance (50), and the second study documented fMRI BOLD signal fluctuations to eye-closure and invasive electrophysiological recordings in primates (51). Although relevant and buttressing the claims made here, these studies did not specifically address the triune relationship between fMRI DFC, eyelid status, and vigilance behavior documented here.…”
Section: Discussionmentioning
confidence: 78%
“…The utility of using SEC in the context of fMRI recordings was recently explored in two studies. The first study documented differences in resting-state fMRI global signal amplitude between eyes-open and eyes-closed states to EEG vigilance (50), and the second study documented fMRI BOLD signal fluctuations to eye-closure and invasive electrophysiological recordings in primates (51). Although relevant and buttressing the claims made here, these studies did not specifically address the triune relationship between fMRI DFC, eyelid status, and vigilance behavior documented here.…”
Section: Discussionmentioning
confidence: 78%
“…In a follow-up study, Wong et al (2015) compared measures of global signal amplitude and EEG vigilance in the eyes-open and eyes-closed states and found that changes (eyes-open minus eyes-closed) in the global signal amplitude were negatively correlated with the associated changes in EEG vigilance. Interestingly, the slope of this relation was found to be similar to that of the previously observed association between caffeine-related changes in the global signal amplitude and EEG vigilance, thus providing evidence for a fundamental relation between global signal amplitude and EEG vigilance.…”
Section: Information In the Global Signalmentioning
confidence: 99%
“…For example, more attentive or vigilant (or caffeinated) human subjects exhibit reduced variance in the global fMRI signal (Wong et al, 2016; Wong et al, 2012, 2013). And psychiatric conditions have been characterized by differences in global fMRI signals, for example by altered variance in subjects with schizophrenia (Hahamy et al, 2014; Yang et al, 2014), or by an altered spatial distribution of the global signal in patients with autism spectrum disorder (Gotts et al, 2013; Gotts et al, 2012).…”
Section: Introductionmentioning
confidence: 99%